Investigating SMEs Performance: Innovation, Leadership, or Investment Driven? - Septy Setia Nugraha (EkBis: Jurnal Ekonomi dan Bisnis, 2021)
The main objective of this study is to find out how much influence the leadership orientation and innovation strategies affect the level of SMEs investment, which has implications for improving firm performance. This research uses structural equation modeling (SEM) analysis tools to test hypotheses. While the data in this study were processed using AMOS software. However, before testing, a goodness-of-fits model test is used to determine whether the data used is following the SEM model. This study uses a data collection tool in the form of a questionnaire that is calculated for each variable; the study sample is Central Java and DI Yogyakarta SMEs. Empirically all the hypotheses in this study is supported, then this research can be concluded as follows, improving the performance of SMEs can be achieved through the implementation of the company's innovation strategy, the company's ability to invest and the company's foresight in conducting high leadership orientation. The better application of innovation strategy and the strength of SME entrepreneurs in their leadership orientation and their courage in increasing investment to increase the company's innovation capability, it will have implications for improving business performance.